Simultaneous Determination of Eight Flavonoids in the Flowers of Matricaria chamomilla by High Performance Liquid Chromatography. (27th November 2019) - Xie, Xiao-Yu; Chen, Fang-Fang; Shi, Yan-Ping
Abstract: An HPLC method was developed for simultaneous determination of five flavones (apigenin, three apigenin 7- O -glucoside acylated derivatives, and luteolin) and three methoxylated flavonols in Matricaria chamomilla . Full validation of the assay was carried out including linearity, LODs, LOQs, precision, repeatability, stability, and accuracy. The results demonstrated that the method developed was simple, accurate, and reliable. Five batches of M. chamomilla samples were determined using the developed method, and total contents of the eight flavonoids ranged from 1.843 to 2.134 mg/g. Among them, the content of apigenin was the highest with values of 0.538 to 0.618 mg/g. In addition, the extract solution from M. chamomilla exhibited a significant dose-dependent inhibition of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) activity, with a 50% inhibition (SC50 ) at a concentration of 3.06 ± 0.09 mg/mL, and the flavonoids apigenin-7- O -(6″-acetyl)-glucoside, luteolin, apigenin, eupatolitin, and chrysosplenol D played an important role in the antioxidant activities of the extract solution from M.chamomilla .